Formation and evolution of intermixing zones in C/Si multilayer under heating - Zhuravel, I.A.; Bugayev, Ye.A.; Penkov, A.V.; Zubarev, E.N.; Sevryukova, V.A.; Kondratenko, V.V. (Functional Materials, 2014)
Formation of intermixing zones, their structure and phase composition in C/Si multilayers in as-deposited state and after annealing are studied. During deposition intermixing zones of ∼ 0.6 m thick are formed at both silicon/carbon and carbon/silicon interfaces. The zone formed at C-on-Si interlayer is denser than adjacent zone due to amorphous SiC nucleation. Both the thickness and the densities of intermixing zones increase with annealing temperature up to 800°C. Silicon carbide is revealed in Si-on-C zone at 700°C. Structure of the zones is still amorphous at 950°C.